Crooked tree [compact disc] - Tuttle, Molly, 1993- (Nonesuch, 2022)
Recorded live at Nashville's Oceanway Studios, this album features collaborations with Sierra Hull, Old Crow Medicine Show, Margo Price, Billy Strings, Dan Tyminski, and Gillian Welch. The album explores Molly Tuttle's lifelong love of bluegrass-a genre she first discovered though her father, a music teacher and multi-instrumentalist, and her grandfather, a banjo player.